OPTIMIZING GROUND SUPPORT SYSTEM (CASE STUDY: TERMINAL 3 SOEKARNO-HATTA INTERNATIONAL AIRPORT) (The Indonesian Journal of Business Administration, 2019)
PT Angkasa Pura II built Ground Support System (GSS) facility at Terminal 3 Soekarno-Hatta Int’l Airport. AP II’s GSS consists of Ground Power Unit (GPU), Pre-Conditioned Air Unit, and Water Service Unit (WSU). The management of GSS facilities is inefficient and GSS business still has low utilization. The research objectives are for optimizing and developing GSS business. The qualitative research conducts by data gathering from interview and examine the company’s documents. Literature review with Business Process Improvement of Six-Sigma model DMAIC and Marketing Mix 4P are used for identifying the business issues and assist to find the solution. According to the Define, Measure, & Analyze phase, the root causes are different second party technician & operator, slow response time, power trip of GPU facility, and lack of promotion activity. The solution conducts through Improvement & Control phase for increasing the GSS utilization, GSS revenue, and GSS value. The first solution is developing GSS monitoring and reporting system. The second solution is developing marketing mix 4P strategy, they are Product by develop GSS product free from defects and guaranteed quality, Place by install WSU automatic time sensor, training, and adding Commercial officers, Promotion by use advertisement, direct marketing, sales promotion, personal selling, and public relation, and Price by charge the tariff by per minute.Keywords: Airport, Business Process Improvement, DMAIC, Ground Support System, Marketing Mix